ESTIMATION THE EFFECTS OF PLASMA ACTIVATED MEDIUM ON SOME COMPONENTS THAT RELATED WITH GROWING BREAST CANCER CELL LINES - Rawnaq Z. Fadhil,; Mouruj A. Al aubaydi,; KadhimA.Aadim, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2024)
This study was aimed to assess the influence of plasma activated medium (PAM) on some parameters of breast cancer cell lines (MCF7 and AMJ13) in comparison to normal adipose-derived stem cells (ASCs). First, nitric oxide (NO) production within the used media (RPMI-1640 and MEM) was examined beyond different exposure time (10,15,20, and 25) minutes directly, and the finding suggested a significant increase in NO with increasing exposure time particularly after 20 and 25 min of irradiation in RPMI, while MEM showed significant results only after 25 min. The metabolic parameters were studied including glucose uptake and lactate dehydrogenase (LDH) activity. The results found a decrease in LDH activity proportional to incubation times, as over incubation to 48 hrs the activity reduced more significantly than the 24 hours with minimal influence on the enzyme activity in the media. Correlated results were demonstrated in glucose results as it’s concentration was elevated in the media with increasing irradiation doses for all three treated cell lines in compared to untreated homologues.